Applications of Blender for Medical Media Production: A Case Study on Texturing of 3D Bone Models - Fakmee, Somkiat; Numwong, Terasut (Siriraj Medical Bulletin, 2024)
This article presents a case study on the use of Blender software for creating medical media, with particular focus on texturing techniques to create a 3D bone model. The purpose of this study is to illustrate how educational media are being developed for use in health science education. In the modern era, the development of medical technology is proceeding at a rapid pace. Hence, applying various kinds of health science educational media is essential for teaching and learning in medical school. 3D application is a technology used for creating educational media for the healthcare industry, especially 3D models of human bones in anatomy. These 3D models were created by using a surface texturing technique that was based on actual bone. These involve a seven-step process that includes analyzing the data, studying 3D modeling in detail, unfolding the surface on a 3D model into a 2D plane to paint or edit the texture on the model by using Stencil. This technique involves the incorporation of photographs of skeletal structures into the 3D skeleton model that precisely resembles the real bone anatomically. Additionally, the software tools allow fine-tuning of color and human bone detail to produce models which appear like the original prototype. The finished product is then exported for quality control before being used in the creation of educational media. The textured surface of the skeletal model closely resembles the original prototype, showcasing how Blender software can be employed for texturing 3D bone models to enhance medical learning materials. Therefore, Blender software used to texture a 3D bone model is an effective way for developing and improving 3D models in health science education.